THEORETICAL FOUNDATIONS OF VERB SEMANTICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
According to theoretical materials, linguistics combines verbs that are semantically close to a smaller class of verbs, but each of them, in addition to the general meaning, reflects different colors, i.e., it is defined as the use of syntax in the performance of different forms.The verbs of the studied subclass can be divided into three subgroups.The first group includes the semantic structures of transform, formulate, formalize, reform, etc. The second group includes verbs containing the components "production, creation" - create, establish, produce, etc.The third group consists of verbs that combine the semantic structure of form, shape, fashion, model, and other features.Secondly, the selection of verbs in this group is of theoretical interest, since most of them are derived from Latin and French, with the exception of the verbs shape, frame, set because they are characteristic of formal and scientific methods.Nevertheless, words conform to the norms of the English language, and this subclass of verbs is formed according to laws common to all verbs. The practical significance of the work is determined by the fact that its results can be applied in the study of courses on theoretical grammar of the English language, cognitive semantics, in the preparation of special courses on syntax and lexical semantics, as well as in teaching practical grammar of the English language.